2001
DOI: 10.1007/s001470000285
|View full text |Cite
|
Sign up to set email alerts
|

Calcineurin-inhibitor induced pain syndrome (CIPS): a severe disabling complication after organ transplantation

Abstract: Bone pain after trans-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
89
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(93 citation statements)
references
References 16 publications
3
89
1
Order By: Relevance
“…Lucas and associates 11 studied 26 renal transplant patients who had isolated musculoskeletal pain owing to cyclosporine use and suggested that the interaction between cyclosporine and glucocorticoids, and the toxicity of cyclosporine metabolites, may contribute to CIPS. Grotz and colleagues 10 hypothesized that calcineurin inhibitor-induced vascular disturbance might lead to an increased permeability of bone marrow vessels with consecutive bone marrow edema. However, bone marrow edema is a nonspecific change of CIPS because it can also occur in osteonecrosis, a joint disorder caused by wear and tear, osteoporosis, ischemia, and tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lucas and associates 11 studied 26 renal transplant patients who had isolated musculoskeletal pain owing to cyclosporine use and suggested that the interaction between cyclosporine and glucocorticoids, and the toxicity of cyclosporine metabolites, may contribute to CIPS. Grotz and colleagues 10 hypothesized that calcineurin inhibitor-induced vascular disturbance might lead to an increased permeability of bone marrow vessels with consecutive bone marrow edema. However, bone marrow edema is a nonspecific change of CIPS because it can also occur in osteonecrosis, a joint disorder caused by wear and tear, osteoporosis, ischemia, and tumors.…”
Section: Discussionmentioning
confidence: 99%
“…The relation between calcineurin inhibitors and bone pain was first reported by Bouteiller and associates in 1989, 9 and it was named calcineurininhibitor-induced pain syndrome by Grotz and colleagues in 2001. 10 The prevalence of CIPS is 1% to 17%, mostly occurring in renal transplant recipients. [10][11][12][13][14][15] The mechanism of CIPS is unknown because it is a rare syndrome, and there is a lack of systematic study about it.…”
Section: Introductionmentioning
confidence: 99%
“…Bone scintigraphy shows increased joint and bone uptake, accentuated at the tarsus. 1 This syndrome was initially recognized in the setting of organ transplantation 1 and then also reported in patients following hematopoietic SCT (HSCT). [2][3][4][5] However, the clinical aspects of CIPS in HSCT remain unclear.…”
mentioning
confidence: 99%
“…In contrast, CIPS often occurs at a late stage (X6 weeks) in solid organ transplantation. 1 The reason for this discrepancy is unclear. Patients with hematological diseases have received many neurotoxic drugs, such as chemotherapeutic agents, before HSCT and they also receive many drugs during their HSCT, which may either contribute to or predispose the patients to this complication including the timing of onset.…”
mentioning
confidence: 99%
See 1 more Smart Citation